Reflecting epochs: a review of social background’s influence on interpersonal communication in contemporary television dramas - Dai, Haocheng; Kasimon, Diyana Nawar; Ang, Lay Hoon (Review of Communication Research, 2024)
Television dramas are vital platforms that reflect societal norms, values, and power dynamics. This study investigates how social backgrounds—such as race, ethnicity, gender, and socio-economic status—affect interpersonal communication in contemporary TV dramas. The primary goal is to analyze how these social identities shape communication patterns and behaviors among characters, revealing underlying power dynamics, stereotypes, and inequalities embedded within television content. By examining the intersectionality of social identities in media narratives, this study aims to deepen the understanding of how media representations impact audience perceptions and societal attitudes. This research includes a comprehensive literature review to explore existing studies on social background representation and communication dynamics in media. Additionally, selected TV dramas were analyzed using content and thematic analysis to identify recurring patterns in character interactions and communication styles. The findings indicate that social backgrounds significantly influence communication and relationship dynamics in television stories, mirroring broader societal norms and reinforcing stereotypes and disparities. This research underscores the importance of promoting diverse, authentic, and inclusive portrayals in media. It also highlights the need for critical media literacy and audience engagement initiatives to challenge stereotypes and advocate for positive social change, ultimately contributing to a more equitable media landscape.